EXPERIMENTAL COMPARE OF THE MECHANICAL PROPERTIES OF PULTRUDED GLASS FIBRE REINFORCED PLASTIC BASED ON POLYESTER AND VINYLESTER RESIN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The main purpose of this study is an experimental investigation and comparison of the mechanical properties of pultruded glass fibre reinforced polymer composite based on polyester and vinylester resin. For this purpose, the specimens were cut from the walls of square tube pultruded profile along to the fibres direction. The mechanical properties of the pultruded composite such as ultimate tensile strength and ultimate bending strength, tensile modulus and flexural modulus were obtained. It was observed that using of vinyl ester resin in pultruded composite instead of polyester resin enhanced the ultimate tensile and flexural strength from ~13% to ~24% in dependence of composite specimen’s thickness.